Immigration and Feminine Diasporic Identity in Emecheta’s Second Class Citizen - Anouar AY; Nour Elhouda BOUZIDI (UNIVERSITÉ MOHAMED BOUDIAF - M’SILA, 2024)
This study looks at how Buchi Emecheta, a Nigerian writer, challenges dominant narratives that have long marginalized the perspectives of African diasporic women in her novel Second Class Citizen (1974). The study examines how Emecheta’s Nigerian protagonist, Adah, encounters the complexities of life as an immigrant in 1960s British society and highlights Adah's marginalization at the intersection of her race, gender, class, and immigrant status. Through a postcolonial feminist reading of the novel, this study aims to explore how women's writings and African diaspora literature can be understood in relation to immigration and negotiating feminine diasporic identities. It highlights marginalized subjectivities and offers important insights into the lived realities of immigrant women of color. The study also examines Adah's cultural hybridity and interculturality that result from her diasporic situation as well as the changes in her identity construction highlighting her feelings of alienation as well as the emergence of feminist resistance to racism and patriarchy
Keywords: African diaspora; feminine identity; immigration; gender; Second Class Citizen